Empirical tests of budget ratcheting and its effect on managers’ discretionary accrual choices - Leone, Andrew J.; Rock, Steve (Journal of Accounting and Economics, 2002)
In this paper, we investigate whether budgets ratchet. Using business-unit data from a large multinational corporation, we find evidence consistent with ratcheting where favorable budget variances result in performance budget increases that are larger than decreases associated with unfavorable variances of the same magnitude. We argue that under ratcheting, the cost of reporting positive transitory earnings surprises outweigh the short-term benefits of the current-period bonus. Consequently, we hypothesize that managers make income-decreasing discretionary accruals to offset transitory earnings surprises beyond the level expected under fixed budgets. Using a proxy for transitory earnings surprise, we find evidence consistent with this hypothesis.